Decomposition of hydrogen sulfide (H2S) on Ni(100) and Ni3Al(100) surfaces from first-principles - Hernandez, Juan Martin; Lim, Dong-Hee; Hoang Viet Phuc Nguyen; Yoon, Sung-Pil; Han, Jonghee; Nam, Suk Woo; Yoon, Chang Won; Kim, Soo-Kil; Ham, Hyung Chul (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
Spin-polarized density functional theory studies of hydrogen sulfide (H2S) adsorption and decomposition on Ni(100) and Ni3Al(100) surfaces were conducted to understand the aluminum (Al) alloying effect on H2S dissociation. For such purpose, we first determined the near surface structure of fully ordered Ni3Al alloy along the [100] direction by calculating the Al segregation energy to the surface and then examined the adsorption energies of the adsorbates (H2S, HS, S, and H) and the activation barriers for the H2S and HS decomposition by using Climbing Image-Nudged Elastic Band method. We found that regardless of the way to terminate the surface, Al atom in bimetallic Ni3Al(100) tends to exist in the first surface layer, rather than in the second or third layer, and the Ni3Al(100) surface can substantially retard the H2S decomposition by reducing the adsorption energy of sulfur compounds compared to the pure Ni(100) case. Finally, we presented how the Al in Ni3Al modifies the activity of surface Ni atoms toward the sulfur compounds by calculating the local density of states and charge distribution in alloying components. This work hints the importance of knowing how to properly tailor the reactivity of Ni based materials to enhance the resistance for sulfur poisoning. Copyright (C) 2014, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: METAL-SURFACES; CARBON-MONOXIDE; ALLOY SURFACES; ADSORPTION; CO; ELECTROOXIDATION; CHEMISORPTION; DISSOCIATION; TEMPERATURE; OVERLAYERS